Rancang Bangun Telegram Chatbot Informasi Puskesmas Cilimus Dengan Natural Language Processing - Elsen, Rickard; Adam Faris, Salman (Jurnal Algoritma, 2025)
A chatbot is a computer program designed to simulate intellectual dialogue with one or more humans, either through text or audio. Chatbots serve specific functions and roles, including simplifying the process of responding to inquiries—where responses are not required to be immediate—and allowing questions to be answered in real time.The objective of this research is to develop an information chatbot for Puskesmas Cilimus to support real-time information services. By using a Natural Language Processing (NLP) approach, the development process helps design and build an application that facilitates interaction between humans and computer systems. The Rational Unified Process (RUP) method is used for system design, which includes the phases of Inception, Elaboration, Construction, and Transition.The result of this study is a Telegram-based information chatbot service that can assist users in accessing information at any time without time constraints.